2002
DOI: 10.1046/j.0016-8025.2001.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of carboxylating enzymes, sucrose metabolizing enzymes and plant hormones in a tropical epiphytic CAM orchid to CO2 enrichment

Abstract: After exposure to a doubled CO 2 concentration of 750 µ µ µ µ L L − − − − 1 for 2 months, average relative growth rate (RGR) of Mokara Yellow increased 25%. The two carboxylating enzymes, ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) and phosphoenolpyruvate carboxylase (PEPCase), responded differently to CO 2 enrichment. There was a significant daytime down-regulation in Rubisco activity in the leaves of CO 2 -enriched plants. However, PEPCase activity in CO 2 -enriched plants was much higher in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…CO 2 could enhance the activity of nitrate reductase in plants (Buchanan et al, 2000), which is a major enzyme in NO synthesis through the nitrite reduction (Yamasaki et al, 1999;Meyer et al, 2005). Alternatively, elevated CO 2 could increase auxin levels (Li et al, 2002;Teng et al, 2006), which then induces NO accumulation . These issues require further investigation, but we propose that elevated CO 2 first increases NO levels in roots by enhancing the nitrate reductase activity and then enhances FER expression.…”
Section: A Possible Role For Nomentioning
confidence: 99%
“…CO 2 could enhance the activity of nitrate reductase in plants (Buchanan et al, 2000), which is a major enzyme in NO synthesis through the nitrite reduction (Yamasaki et al, 1999;Meyer et al, 2005). Alternatively, elevated CO 2 could increase auxin levels (Li et al, 2002;Teng et al, 2006), which then induces NO accumulation . These issues require further investigation, but we propose that elevated CO 2 first increases NO levels in roots by enhancing the nitrate reductase activity and then enhances FER expression.…”
Section: A Possible Role For Nomentioning
confidence: 99%
“…However, divergent results about the influence of elevated CO 2 in CAM plants have been reported during the last decades [147][148][149][150][151][152][153], demonstrating that the enrichment of CO 2 into the atmosphere can trigger complex responses in CAM plants. For example, elevated CO 2 had no effect on diel CO 2 uptake by Kalanchoë daigremontiana [147] nor on nighttime CO 2 uptake in Clusia uvitana and Portulacaria afra [154,155], whereas in several other CAM species more significant impacts of elevated CO 2 on the daytime, nighttime and/or diel carbon acquisition have been reported [148,150,151,153]. Changes in morphology, anatomy and biochemistry driven by modifications in atmospheric CO 2 concentration have also been observed in some CAM plants, commonly associated with concomitant alterations in their growth rates and biomass accumulation.…”
Section: Bromeliads and Agaves Cam Plants In A Climate Change And Desmentioning
confidence: 99%
“…16,19,20 Recent studies showed that elevated CO 2 increased auxin level and response, 2,3,21 and that production of NO was promoted in tomato roots under co-treatment with elevated CO 2 and iron deficiency. 11 Consequently, in this paper, we proposed that cross-talks between NO and Ca 2+ involving in elevated CO 2 induced LR formation.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%